Stock Market Intermediaries - Vidal Ramírez, Fernando (1973)
The concept of commercial mediators, in its various forms, was first introduced and regulated within the Peruvian legal system by the Code of Commerce of 1902. This code offered a definition of commercial mediation. Subsequently, Decree Act 18302 altered its nomenclature, referring to them as intermediaries. This paper aims to ascertain the legal classification of intermediaries, leveraging the innovations introduced by recent legislation in the stock market. It proceeds to analyze the implementation of this new legislation to delineate both its legal framework and the legal classification of intermediary activities.